2019
DOI: 10.1186/s42492-019-0017-6
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-curvature functional based digital high pass filter of the bivariate cubic B-spline model polynomial function

Abstract: This research addresses the design of intensity-curvature functional (ICF) based digital high pass filter (HPF). ICF is calculated from bivariate cubic B-spline model polynomial function and is called ICF-based HPF. In order to calculate ICF, the model function needs to be second order differentiable and to have non-null classic-curvature calculated at the origin (0, 0) of the pixel coordinate system. The theoretical basis of this research is called intensitycurvature concept. The concept envisions to replace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…T2‐weighted MRI is not indicated for vessel imaging, and in this context, the paper proposes a technique able to improve vessels detection in T2‐MRI. This aspect is not reported elsewhere and is thus the main novelty of this research vs recent developments 27‐30 . Moreover, this research makes a neat progress vs the inverse Fourier transformation procedure reported earlier 28 .…”
Section: Discussion Of the Contributionmentioning
confidence: 62%
See 4 more Smart Citations
“…T2‐weighted MRI is not indicated for vessel imaging, and in this context, the paper proposes a technique able to improve vessels detection in T2‐MRI. This aspect is not reported elsewhere and is thus the main novelty of this research vs recent developments 27‐30 . Moreover, this research makes a neat progress vs the inverse Fourier transformation procedure reported earlier 28 .…”
Section: Discussion Of the Contributionmentioning
confidence: 62%
“…Improvement of vessel detection in T2‐MRI and change of contrast of T2‐MRI and MRA are caused by sharpening effect of ICF and reconstructed ICF images. Present state of knowledge in intensity‐curvature image processing is based on evidence provided in support to the use of ICF as image space and k‐space filter 27‐30 . The main contribution of this research is the signal processing technique illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations